The Tryout of Dance Teaching Media in Public School in The Context of Appreciation and Creation Learning - Malarsih, Malarsih (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
Dance learning through appreciation and creation approach is considered important in public school. This study is aiming at realizing dance media to be used as a tool to educate students as formulated in the school curriculum. Specific target to be accomplished in this study is the realization of dance learning media as one of appreciation and creation educational tool in public school. Further, this study employed developmental research method. The tryout of the product was done to measure the effectivity and creativity of students while the media is implemented in dance learning. The product’s trial result showed that the use of dance learning media that was designed specifically for appreciation and creation approach has succesfully driven the students to be more active and creative. Teacher assistant was less needed by students whenever they have problems related to the dance learning.How to Cite: Malarsih. (2016). The Tryout of Dance Teaching Media in Public School in The Context of Appreciation and Creation Learning. Harmonia: Journal of Arts Research And Education, 16(1), 95-102. doi:http://dx.doi.org/10.15294/harmonia.v16i1.4561